2017
DOI: 10.1002/ecy.1647
|View full text |Cite
|
Sign up to set email alerts
|

Refuge quality impacts the strength of nonconsumptive effects on prey

Abstract: Prey often retreat into the safety of refuges for protection from predators. This shift into refuge can reduce foraging opportunities, escalating the costs of risk and the strength of nonconsumptive effects. Such costs, however, may be shaped by the variation in resources that refuges harbor for prey foraging (i.e., refuge quality), and change dynamically via impacts on prey state. Despite its potential importance, we lack an explicit understanding of how refuge quality impacts prey performance under risk. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 70 publications
2
32
1
Order By: Relevance
“…The effects of current risk on the growth efficiency of wave‐exposed snails are consistent with our previous work (Donelan et al. ), but we were surprised to find similarly strong effects for sheltered snails. As suggested above, snails from sheltered shores may be plastic in response to risk as one‐year‐olds because direct exposure to predators continues to be stressful regardless of prey's expectations for risk.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The effects of current risk on the growth efficiency of wave‐exposed snails are consistent with our previous work (Donelan et al. ), but we were surprised to find similarly strong effects for sheltered snails. As suggested above, snails from sheltered shores may be plastic in response to risk as one‐year‐olds because direct exposure to predators continues to be stressful regardless of prey's expectations for risk.…”
Section: Discussionsupporting
confidence: 92%
“…Predation risk is known to reduce prey growth efficiency in this (Trussell et al 2006) and other (McPeek 2004) systems, likely because prey must allocate energy to support costly stress molecules and physiological pathways rather than allocating energy to growth (Pauwels et al 2005, Slos andStoks 2008). The effects of current risk on the growth efficiency of wave-exposed snails are consistent with our previous work (Donelan et al 2017), but we were surprised to find similarly strong effects for sheltered snails. As suggested above, snails from sheltered shores may be plastic in response to risk as one-year-olds because direct exposure to predators continues to be stressful regardless of prey's expectations for risk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A second complementary approach is to focus on vegetation manipulations to increase available nutrition (e.g., thinning of dense forest stands). Recent work in marine systems has shown that the non-consumptive effects prey incur in seeking refuge from predators decline with the foraging resources those refuges contain (Donelan et al 2017). Together, these tools can help incentivize elk to stay on public lands by improving the quality of security areas, thus potentially increasing opportunity for hunters to pursue elk on public lands and reducing conflict between elk and private landowners.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Such nonconsumptive predator effects ("NCEs") on prey foraging activity may diminish competition by increasing relative resource availability and/or reducing agonistic interactions between prey individuals (Abramsky, Rosenweig, & Subach, 1998;Kohler & McPeek, 1989;Kotler & Holt, 1989;Werner & Anholt, 1996). By contrast, NCEs causing habitat shifts may enhance competition for refuge habitats and food located within or adjacent to refuges (Donelan, Grabowski, & Trussell, 2017;Moody, Houston, & McNamara, 1996;Olsson, Brown, & Helf, 2008;Orrock et al, 2008).…”
Section: Introductionmentioning
confidence: 99%